Dentistry students' experiences, engagement and perception of biochemistry within the dental curriculum and beyond. (12th October 2020) - Youhanna, Karla Mariah Yumul; Adam, Lee; Monk, Brian C.; Loch, Carolina
Abstract: Introduction/Objectives: Basic knowledge at the molecular level is necessary to care for the orofacial complex as part of the whole body. Many undergraduate dentistry students struggle to engage with biochemistry during the degree due to difficulty in appreciating the relevance of biochemistry to clinical practice. This study investigated student experiences, perception and engagement with biochemistry as part of the dental curriculum and explored how the teaching of biochemistry might be further developed. Methods: Focus groups were conducted with 21 participants, in groups of four to six students from the 3rd year to 5th year, as well as with recent graduates and post‐graduate students from a prominent Australasian dental school. Data were analysed using a general inductive approach. Results: Focus group participants viewed the oral biochemistry module as well organised and professionally run. However, participants reported that the large amount of material taught in the module made them feel overwhelmed and demotivated. Biochemistry was regarded by undergraduate participants as relevant to dental practice, but graduate participants thought it was only relevant to those sitting examinations for further training. Biochemistry was perceived as most relevant to dental research and expanding scientific literacy. Discussion/Conclusions: Participants in this study suggested that reducing the amount of material taught, focusing on dentally relevant biochemical concepts and overtly stating the connection of biochemistry to clinical practice could increase engagement and enhance the module within the dental curriculum.